Mediating roles of leukoaraiosis and infarcts in the effects of unilateral carotid artery stenosis on cognition - Huang, Kuo-Lun; Chang, Ting-Yu; Wu, Yi-Ming; Chang, Yeu-Jhy; Wu, Hsiu-Chuan; Liu, Chi-Hung; Lee, Tsong-Hai; Ho, Meng-Yang (Frontiers in Aging Neuroscience, 2022)
Background and Objectives: Leukoaraiosis and infarcts are common in patients with carotid artery stenosis (CAS), and CAS severity, leukoaraiosis and infarcts all have been implicated in cognitive impairments. CAS severity was not only hypothesized to directly impede specific cognitive domains, but also transmit its effects indirectly to cognitive function through ipsilateral infarcts as well as periventricular leukoaraiosis (PVL) and deep white matter leukoaraiosis (DWML). We aimed to delineate the contributions of leukoaraiosis, infarcts and CAS to different specific cognitive domains. Method: 161 participants with unilateral CAS (>50%) on the left (n=85) or right (n=76) side and 65 volunteers without significant CAS (<50%) were recruited. The PVL, DWML, and infarct severity were visually rated on MRI. A comprehensive cognitive battery was administered and standardized based on age norms. Correlation and mediation analyses were adopted to examine the direct and indirect influence of CAS, leukoaraiosis and infarct on specific cognitive domains with adjustment for education, hypertension, diabetes mellitus and hyperlipidemia covariates. Results: CAS severity was associated with ipsilateral leukoaraiosis and infarct extent. Left CAS had direct effects on most cognitive domains, except for visual memory and constructional ability, and transmitted its indirect effects on all cognitive domains through ipsilateral PVL, and on constructional ability and psychomotor through infarcts. Right CAS only had negative direct effects on visual memory, psychomotor, design fluency and color processing speed, and transmitted its indirect effects on visual memory, word and color processing speed through ipsilateral infarcts. The trends of direct and indirect cognitive effects remained similar after covariate adjustment. Conclusion: Left and right CAS would predominantly lead to verbal and non-verbal cognitive impairment respectively, and such effects could be mediated through CAS-related leukoaraiosis and infarct. Given that cognition is subject to heterogenous pathologies, the exact relationships between LVD and SVD markers and their composite prognostic effects on cognition requires further investigation.